Efficiency at Maximum Power of a Carnot Quantum Information Engine - Fadler, Paul; Friedenberger, Alexander; Lutz, Eric (Physical Review Letters, 2023)
Optimizing the performance of thermal machines is an essential task of thermodynamics. We here consider the optimization of information engines that convert information about the state of a system into work. We concretely introduce a generalized finite-time Carnot cycle for a quantum information engine and optimize its power output in the regime of low dissipation. We derive a general formula for its efficiency at maximum power valid for arbitrary working media. We further investigate the optimal performance of a qubit information engine subjected to weak energy measurements.
CRIS-Team Scopus Importer:2023-08-04

Nonequilibrium information erasure below kTln2 - Konopik, M.; Friedenberger, Alexander; Kiesel, N.; Lutz, E. (EPL - Europhysics Letters, 2020)
Landauer's principle states that information erasure requires heat dissipation. While Landauer's original result focused on equilibrium memories, we here investigate the reset of information stored in a nonequilibrium state of a symmetric two-state memory. We derive a nonequilibrium generalization of the erasure principle and demonstrate that the corresponding bounds on heat and work may be reduced to zero. We further introduce reset protocols that harness energy and entropy of the initial preparation and so allow to reach these nonequilibrium bounds. We finally provide numerical simulations with realistic parameters of an optically levitated nanosphere memory that support these findings. Our results indicate that local dissipation-free information reset is possible away from equilibrium.
CRIS-Team Scopus Importer:2020-11-20

Quantum witness of a damped qubit with generalized measurements - Bojer, Manuel; Friedenberger, Alexander; Lutz, Eric (Journal of Physics Communications, 2019)
We evaluate the quantum witness based on the no-signaling-in-time condition of a damped two-level system for nonselective generalized measurements of varying strength. We explicitly compute its dependence on the measurement strength for a generic example. We find a vanishing derivative for weak measurements and an infinite derivative in the limit of projective measurements. The quantum witness is hence mostly insensitive to the strength of the measurement in the weak measurement regime and displays a singular, extremely sensitive dependence for strong measurements. We finally relate this behavior to that of the measurement disturbance defined in terms of the fidelity between pre-measurement and post-measurement states.
CRIS-Team WoS Importer:2019-07-09